Research Trends of Augmented Reality in Biology Learning: Content and Bibliometric Mapping Analysis - Hartono, Hartono; Wilsa, Asrizal Wahdan; Subali, Bambang; Rahayu, Enni Suwarsi (UUM Press, 2025)
Purpose - Through the use of content analysis, this study was aimed at identifying the patterns in research conducted during the past decade and investigating the bibliometric outcomes of articles focused on augmented reality (AR) utilization in biology learning. Methodology - This study conducted a bibliometric analysis. To perform the bibliometric mapping analysis, 116 articles were reviewed. A total of 111 articles published between 2014 and 2023 in the Scopus database were selected for the content analysis. The bibliometric analysis centered on 69 selected articles. Findings - The most frequently used keywords in these articles were “AR,” “development,” and “application.” Furthermore, among the articles reviewed, it was observed that there was a recent focus on marker-based material on paper. This finding indicates that the focus of the latest articles is AR media modeling, use, comparison with conventional media, and AR development in a biology learning context. Saidin, Iftene, and Bonete were the most frequently cited authors in this field. The content analysis shows that development and practical guidance have been the most extensively examined variables in the articles. Development and experimental studies were the most frequently used research designs in the last ten years. Significance - Future research in this field will be improved by using mixed-methods examining variables that enhance students’ interpersonal skills, and not just by developing and knowing the extent to which users can operate AR applications